Heterostructures CdS/porous-Si and CdS/porous-CdTe for the manufacture of photovoltaic cells - Diadenchuk, Alona; Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Kidalov, V. V. (My University, 2017)
In this paper the receipt of CdS thin films on substrates porous-Si and porous-CdTesurface by chemical vapor deposition later use of the structures for the production of photovoltaic cells
Keywords: receipt of CdS; substrates porous-Si; porous-CdTesurface